Changes in Domestic Emissions Impact on Provincial PM2.5 and NO2 Concentrations during the 1st to 4th Seasonal PM Management Periods 1~4차 미세먼지 계절관리제 기간 시도별 PM2.5 및 NO2 농도에 대한 국내 배출영향 변화 - Seo, Jiwon; Kang, Yoon Hee; Kim, Eunhye; Jeong, Seongeun; Kim, Jihun; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2024)
In this study, we quantified changes in domestic emissions impact on PM2.5 and NO2 concentrations in South Korea during the 1st to 4th Seasonal Particulate Matter Management (SPM) periods using observations and air quality simulations. During the entire SPM periods, reductions in domestic emissions impact, the combined effect of changes in emissions and meteorological conditions, contributed an average nationwide decrease of 1.5 μg/m3/year for PM2.5 and 0.9 ppb/year for NO2. The implementation of SPM, coupled with changes in meteorology and unexpected societal issues such as the COVID-19 pandemic, resulted in a decrease of domestic PM2.5 emissions impact by 61.2% throughout the SPM periods. On a provincial level, the decreases in PM2.5 and NO2 concentrations due to the reduction in domestic emissions ranged from 0.1 to 2.6 μg/m3 and 0.3 to 1.9 ppb, respectively, showing a correlation coefficient of 0.60 between them. When a nitrogen oxidation ratio of 0.2 from previous studies was applied, the decrease in domestic NOx emissions impact during the periods accounted for approximately 40% of the nationwide reduction in PM2.5 domestic emissions impact. These findings suggest a high possibility that the decrease in PM2.5 concentrations in South Korea was affected by various precursor emission changes and interprovincial emissions impacts. Therefore, considering the complicated nature inherent in secondary air pollutants such as PM2.5, it becomes increasingly essential to establish a comprehensive analysis platform to integrate various information such as emissions, observations, and air quality simulations. This integration is crucial for more adequately developing control strategies for air pollution problems that we are facing. Additionally, from a health perspective, the magnitude of reduced PM2.5 and NO2 emissions impacts varied among provinces. Therefore, developing strategies tailored to regional conditions, considering both achieving national ambient air quality standards and promoting public health, appears crucial.
Keywords: Domestic emissions impact; emission-observation-modeling-integrating analysis; NOx emissions reduction; Precursor emissions; Seasonal PM management